2016
DOI: 10.1089/gtmb.2015.0028
|View full text |Cite
|
Sign up to set email alerts
|

Stress, COMT Polymorphisms, and Depressive Symptoms in Older Australian Women: An Exploratory Study

Abstract: Objectives: This exploratory study examined the association between exposure to stressful life events (SLEs), polymorphisms (rs165774 and rs4680) in the catechol-O-methyltransferase COMT gene, and risk of depression in women. Methods: A cross-sectional design gathered information from 150 Australia women, aged 60-70 years, on socio-demographics, SLEs, and depressive symptoms. Participants also provided buccal cell swabs for genetic analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…For COMT rs165774, the A allele is associated with lower COMT activity compared with the G allele [31]. In line with this view, the present results suggest that A-allele carriers may be more vulnerable to childhood adversity, as indicated by their higher levels of irrational beliefs (but see [43]). The polymorphism OXTR rs5357 has not been functionally characterized, but a previous candidate gene study found that childhood maltreatment was associated with depressive symptoms only in G-allele carriers [44].…”
Section: Discussionsupporting
confidence: 83%
“…For COMT rs165774, the A allele is associated with lower COMT activity compared with the G allele [31]. In line with this view, the present results suggest that A-allele carriers may be more vulnerable to childhood adversity, as indicated by their higher levels of irrational beliefs (but see [43]). The polymorphism OXTR rs5357 has not been functionally characterized, but a previous candidate gene study found that childhood maltreatment was associated with depressive symptoms only in G-allele carriers [44].…”
Section: Discussionsupporting
confidence: 83%
“…Lastly, allelic variations of the catechol-O-methyltransferase ( COMT ) gene, which is involved in the degradation of catecholamine neurotransmitters (i.e., dopamine, norepinephrine, and epinephrine), have effects on mood, emotion processing, and perception of well-being, as well as pain sensitivity across a number of populations (Belfer & Segall, 2011; Wichers et al, 2008). Even with relatively small sample sizes, research has shown trends for patients with the Val158Met (rs4680) COMT polymorphism to have increased risk for persistent postsurgical pain and incidence of depressive symptoms (Hickey et al, 2011; Seib et al, 2016). Recent data also suggest an interaction effect of BDNF signaling and COMT on human cortical plasticity at the cellular and behavioral levels of analysis (Witte et al, 2012).…”
mentioning
confidence: 99%
“…Associations of rs165774 were also found by Higashiyama et al in patients with schizophrenia vs. healthy controls and by Seib et al in older women with depression. 29,30 Ittiwut et al found an association between rs4680 and c.615+1354C>T (rs174696) in European American patients with cocaine-induced paranoia. 31 In our current study we have investigated a possible existence of an association between rs4680, rs6269, rs4633, rs4818, rs769224, rs165774, as well as rs174696 and levodopa-induced dyskinesia in 232 Caucasian PD patients from the neurological department of the Siberian State University Hospital of Tomsk, Russian Federation.…”
Section: Introductionmentioning
confidence: 99%